Analisis continuance usage intention pada penggunaan e-Wallet dengan information use fairness sebagai moderasi - Putra, Edy Yulianto; Nicholas, Nicholas; Ariyanto, Hepy Hefri (Nur Science Institute, 2025)
This study aims to analyze the factors influencing the continuance usage intention (CUI) of e-wallet users in Batam, focusing on the effects of reputation, social media activeness, satisfaction, and information use transparency. Data was collected in Batam using a sample of five e-wallet applications, namely OVO, Gopay, ShopeePay, Dana, and LinkAja, with purposive sampling through an online questionnaire. This study used the SEM-SEM analysis method. The results indicate that reputation and social media activeness do not significantly impact users' CUI, while satisfaction has a positive and significant effect. Additionally, information use transparency was found to reduce fear of identity theft, contributing to users' decision to continue using e-wallets. Information use fairness was also found to have a significant adverse effect on the relationship between fear of identity theft and CUI, suggesting that the fair use of personal data reduces users' concerns. These findings provide new insights for e-wallet providers in designing strategies to enhance user loyalty, particularly by considering transparency and fairness in managing personal data.